2019
DOI: 10.3390/molecules24081587
|View full text |Cite
|
Sign up to set email alerts
|

Anticandidal Potential of Stem Bark Extract from Schima superba and the Identification of Its Major Anticandidal Compound

Abstract: Plant-derived extracts are a promising source of new drugs. Schima superba is traditionally used in China for heat clearing, detoxification, and treatment of furuncles. In this study, the anticandidal properties and mechanism of action of S. superba (SSE) were explored using a stem bark extract. SSE possessed high polyphenol and saponin contents of 256.6 ± 5.1 and 357.8 ± 31.5 µg/mg, respectively. A clear inhibition zone was observed for C. albicans growth through the disc diffusion method and the 50% inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Chemical analyses showed that Schima spp. contain triterpenoids and saponins as well as flavonoids and anthocyanins (Deng et al, 2010, Kitagawa et al, 1975, Liang et al, 2019, Liu et al, 2019, Wu et al, 2019, Wu et al, 2015, Yang et al, 2018, Yu et al, 2019). Daphniphyllum oldhamii (Hemsl.)…”
Section: Methodsmentioning
confidence: 99%
“…Chemical analyses showed that Schima spp. contain triterpenoids and saponins as well as flavonoids and anthocyanins (Deng et al, 2010, Kitagawa et al, 1975, Liang et al, 2019, Liu et al, 2019, Wu et al, 2019, Wu et al, 2015, Yang et al, 2018, Yu et al, 2019). Daphniphyllum oldhamii (Hemsl.)…”
Section: Methodsmentioning
confidence: 99%
“…Chemical analyses showed that Schima spp. contain triterpenoids and saponins as well as flavonoids and anthocyanins (Deng et al, 2010;Kitagawa et al, 1975;Liang et al, 2019;Liu et al, 2019;Wu et al, 2015Wu et al, , 2019Yang et al, 2018;Yu et al, 2019).…”
Section: Target Tree Speciesmentioning
confidence: 99%
“…Kaempferol 3-rhamnoside (KR, Figure 1A) is a flavonol glycoside extracted from the bark of Schima superba, which is a broad-leaved evergreen tree of the Camellia family, and widely used in traditional Chinese medicine for heat clearing, detoxification, and furuncle treatment [13]. The antitumor, anti-inflammatory, antioxidant, antibacterial, anticandidal, antiobesity, and hepatoprotective properties of KR have been documented in several bioassays [14][15][16][17][18][19]. However, the biological targets and effects of KR on the CNS are largely unknown.…”
Section: Introductionmentioning
confidence: 99%